Output gap and Neutral interest measures for Colombia based on semi-structural models - Ocampo Díaz, Sergio (2012)
In this paper two new measures of the Colombian output gap and the real neutral interest rate are proposed. Instead of relying only on statistical filters, the proposed measures use semistructural New-Keynesian models, adapted for a small open economy. The output gap measures presented are in line with previous works for Colombia and capture all the turning points of the Colombian business cycle, as measured by Alfonso et al. (2011). They are also strongly correlated with inflation and precede its movements along the sample. The neutral interest rate computed indicates that the monetary policy stance has been overall countercyclical, but has failed to anticipate the output gap s movements, or at least react strongly enough to them.